Political Inheritance of Pakistan - Low, D. A. author. aut Link
VIII, 292 p.
Keywords: Based on papers originally presented at a conference in Churchill College, Cambridge, this book discusses the pre-independence history of those areas of the South Asian sub-continent that territorially became the Pakistan of 1947. Titles in the series include "South Africa: A Modern History".